Blind search for 21-cm absorption systems using a new generation of Chinese radio telescopes. (May 2017) - Yu, Hao-Ran; Pen, Ue-Li; Zhang, Tong-Jie; Li, Di; Chen, Xuelei
Abstract: Neutral hydrogen clouds are known to exist in the Universe, however their spatial distributions and physical properties are poorly understood. Such missing information can be studied by the new generation of Chinese radio telescopes through a blind search of 21-cm absorption systems. We forecast the capabilities of surveys of 21-cm absorption systems by two representative radio telescopes in China –the Five-hundred-meter Aperture Spherical radio Telescope (FAST) and Tianlai 21-cm cosmology experiment (Tianlai). Facilitated by either the high sensitivity (FAST) or wide field of view (Tianlai) of these telescopes, more than a thousand 21-cm absorption systems can be discovered in a few years, representing orders of magnitude improvement over the cumulative discoveries in the past half a century.